Understanding Management Accountants' Satisfaction: A Conceptual Study - Nikhil Chandra Shil; Mahfuzul Hoque; Mahmuda Akter (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Purpose- The study attempts to explain management accountants' satisfaction in terms of the job they do and the system they use, develops a profile of factors impacting such satisfaction, and analyzes the implications of satisfaction on contextual factors like value creation, profitability etc. Design / Methodology / Approach- Based on a structured questionnaire survey, the study deploys a quantitative research methodology to identify the satisfiers of management accountants covering a rich profile of respondents from 113 manufacturing firms having their headquarters located in Dhaka, the capital city of Bangladesh. Contingency approach primarily leads to develop the basic theme of the study and it adopts positivistic paradigm of quantitative research. The results are analyzed through different descriptive and inferential statistical tools to draw conclusions through inductive method. Findings- Management accountants' satisfaction is influenced by several factors which confirms the findings of other studies done on job satisfaction of employees. However, this study reveals that management accountants' satisfaction does not depend on the system they use. This provides a scope for further study. Another important finding of the study that brings significant concern is that the satisfaction of management accountants fails to explain the changes in profitability of the firm. Practical implications- Management accountants are strategic partners to lead any venture towards success, but their satisfaction level was not studied before separately. This may be a reference work for future researchers who want to extend their studies in this area. At the same time, the findings of the study bring some modifications to the existing thoughts, like management accountants are indifferent on management accounting systems they use; management accountants share same motivators with other employees; and management accountants' satisfaction fails to cause profitability of the firms. Thus, the study brings some promising areas for policy makers, researchers, and accounting professionals to commission particular research projects. Originality / Value- Studying job satisfaction and its impact on turnover intention and commitment are old fashioned research area. Factors affecting management accountants' satisfaction and implication of such satisfaction are new areas of research which is an important value addition to the current body of knowledge.
Keywords: M41; 650; management accountants; profitability; satisfaction; conceptual